Integrasi Nilai-Nilai Hadis dalam Tradisi Palang Pintu Pada Budaya Betawi - Rizky Wahyu Satria; Ridwan Hapani; Muhammad Alif; Maftuh Ajmain (Madani: Jurnal Ilmiah Multidisiplin, 2025)
The Palang Pintu tradition is a Betawi wedding ceremonial procession with profound social and spiritual significance. This research aims to explore the integration of hadith values within this tradition through a qualitative approach utilizing field studies and literature review. The research was conducted in Jakarta through in-depth interviews with customary leaders and relevant literature studies. The findings reveal that the Palang Pintu tradition contains fundamental values from hadith teachings, including the concepts of deliberation, mutual respect, equality, and constructive dialogue in resolving social issues. These values are reflected in the dialogue mechanism between the bride and groom's entourages, which prioritizes ethics and civility. The research concludes that the Palang Pintu tradition possesses deep spiritual significance and can serve as a model for integrating local wisdom with Islamic principles.